The concept of social role of the library in Finland - Glosienė, Audronė (Information & Media, 1994)
The article results from the study and research program carried out 1993. 10.10 - 12.31 at the Department of Library and Information Science, University of Oulu, Finland. The program was financed by CIMO (Centre for International Mobility) grant. The author would like to express her gratitude to both institutions for help and assistance. The goal of the program was to get acquainted with the Finnish public library system and to investigate definitions of its societal role. The strategy of the research was multifaceted. Such methods as literature survey and analysis of statistical data were used in combination with formal and informal interviews and observation. An attempt was made to clarify the reflections of public library’s place and role in the society presented by librarians themselves, researchers and professors in the field of LIS, by library experts and officials. This is a case study with elements of comparative analysis. Several factors - such as social, economic, demographic, cultural, religious - are presented as important for the development of Finnish public libraries. The new Library Act (Jan. 1994) and economic crisis are influencing greatly the scope of libraries activities. It makes rethinking the library’s responsibilities towards the society and refining the priorities extremely actual. Several concepts in reflection of public library mission and overall tasks are traditional - the public library in Finland as in many other countries and Nordic ones especially - is seen as democratic cultural institution with the strong orientation to support education and to disseminate information. Tradition is one of the cornerstones of Finnish public libraries. Another one is defined as mobility, openness, responsiveness to societal and professional changes and challenges. Nowadays, public library’s goals are formulated in such a way which stresses their orientation not only to the society (libraries for all) but to every individual (libraries for each). Individualisation of library’s profile and scope of activities is taking place. Library is very strong and visible institution in community life. Such definition becomes very important in the context of decentralisation. Public libraries in Finland are very innovative in professional sense and are able to meet the needs of modern society. In comparison with Lithuanian public libraries, Finnish ones are more open and democratic, their mission is more clearly understood by librarians and the message about the public library is presented to the society in more relevant and articulated way. It should be also stressed that Finnish public libraries are able to set priorities and their services to certain groups of patrons are more targeted. The concept of the societal role of the public library in Finland could be defined as pluralistic and holistic, reflecting the mentality of post-industrial society.